The current status of an FDG-PET cancer screening program in Japan, based on a 4-year (2006-2009) nationwide survey - Minamimoto, Ryogo; Senda, Michio; Jinnouchi, Seishi; Terauchi, Takashi; Yoshida, Tsuyoshi; Murano, Takeshi; Fukuda, Hiroshi; Iinuma, Takeshi; Uno, Kimiichi; Nishizawa, Sadahiko; Tsukamoto, Eriko; Iwata, Hiroshi; et al. (Annals of nuclear medicine, 2013)
Objective The aim of this study was to survey the 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET) cancer screening program conducted in Japan. Methods The “FDG-PET cancer screening program” included both FDG-PET and positron emission tomography with computed tomography (PET/CT) with or without other combined screening tests that were performed for cancer screening in asymptomatic subjects. A total of 155,456 subjects who underwent the FDG-PET cancer screening program during 2006–2009 were analyzed. Results Of the 155,456 subjects, positive findings suggesting possible cancer were noted in 16,955 (10.9 %). The number of cases with detected cancer was 1,912 (1.23 % of the total screened cases, annual range 1.14–1.30 %). Of the 1,912 cases of detected cancer, positive findings on FDG-PET were present in 1,491 cases (0.96 % of the total number of screened cases). According to the results of further examinations, the true positive rate for subjects with suggested possible cancer (positive predictive value) was 32.3 % with FDG-PET. Cancers of the colon/rectum, thyroid, lung, and breast were most frequently found (396, 353, 319, and 163 cases, respectively) with high PET sensitivity (85.9, 90.7, 86.8, 84.0 %, respectively). Prostate cancer and gastric cancer (165 and 124 cases, respectively) had low PET sensitivity (37.0 and 37.9 %, respectively). The Union for International Cancer Control (UICC) clinical stage of cancer found with the FDG-PET cancer screening program was mainly Stage I. Conclusions The FDG-PET screening program in Japan has detected a variety of cancers at an early stage. However, several cancers were found in repeated FDG-PET cancer screening program, indicating the limitation of a one-time FDG-PET cancer screening program. The value of the FDG-PET cancer screening program is left to the judgment of individuals with regard to its potentials and limitations.